A Curative‐Intent Trimodality Approach for Isolated Abdominal Nodal Metastases in Metastatic Colorectal Cancer: Update of a Single‐Institutional Experience. (14th February 2018) - Johnson, Benny; Jin, Zhaohui; Haddock, Michael G.; Hallemeier, Christopher L.; Martenson, James A.; Smoot, Rory L.; Larson, David W.; Dozois, Eric J.; Nagorney, David M.; Grothey, Axel
Abstract : Background: The purpose of this study was to define survival rates in patients with isolated advanced abdominal nodal metastases secondary to colorectal cancer (CRC), treated with curative‐intent trimodality therapy. Materials and Methods: Sixty‐five patients received trimodality therapy, defined as chemotherapy delivered with external beam radiotherapy (EBRT) followed by lymphadenectomy and intraoperative radiotherapy (IORT). Infusional 5‐fluorouracil was the most common radiosensitizer used (63%, 41 patients). The median dose of EBRT was 50 Gy, and the median dose of IORT was 12.5 Gy. We evaluated time to distant metastasis, toxicities, local failure within the EBRT field, recurrence within the IORT field, and survival. Results: Fifty‐two percent of patients were male; patients' median age was 50.5 years. All patients had an Eastern Cooperative Oncology Group score ≤1. Twenty‐nine patients had right‐sided colon cancer, 22 had left‐sided colon cancer, and 14 had rectal primaries. The median time from initial CRC diagnosis to development of abdominal nodal metastatic disease was 20.6 months (95% confidence interval [CI], 21.2–40.8 months). Seventy‐eight percent (51 patients) had para‐aortic nodal metastases, 15% (10 patients) had mesenteric nodal metastases, and 6% (4 patients) had both. With a median follow‐up of 77.6 months, the median overall survival and 5‐year estimated survival rate were 55.4 months (95% CI, 47.2–80.9 months) and 45%, respectively. The median progression‐free survival was 19.3 months (95% CI, 16.5–32.8 months). Twenty‐six (40%) patients never developed distant disease. The outcome was not affected by disease sidedness or rectal primary. Treatment was well tolerated without grade 3 or 4 toxicities. Conclusion: Trimodality therapy produces sustainable long‐term survival in selected patients with metastatic CRC presenting with isolated retroperitoneal or mesenteric nodal relapse. Implications for Practice: This article reports a unique trimodality approach incorporating external beam radiotherapy with radiosensitizing chemotherapy, surgical resection, and intraoperative radiotherapy provides durable survival benefit with significant curative potential for patients with metastatic colorectal cancer who present with isolated abdominal nodal (mesenteric and/or retroperitoneal) recurrence. Abstract : This article reports an update on a unique approach to the management of isolated abdominal lymph node metastasis (retroperitoneal or mesenteric) in metastatic colorectal cancer. The three‐prong approach incorporates external beam radiotherapy with radiosensitizing fluoropyrimidine‐based chemotherapy followed by lymphadenectomy and intraoperative radiotherapy to achieve cure in patients with advanced isolated abdominal metastases.